Coexistence of DIPNECH and carotid body paraganglioma: is it just a coincidence?. (13th May 2020) - Pedro, J; Cunha, F M; Neto, V; Hespanhol, V; Martins, D F; Guimarães, S; Varela, A; Carvalho, D
Abstract : Summary: We describe the case of a 56 year-old woman with the almost simultaneous appearance of diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) and a carotid body paraganglioma. Of interest, 6 years earlier, the patient underwent total thyroidectomy due to papillary thyroid carcinoma and, in the meantime, she was submitted to mastectomy to treat an invasive ductal carcinoma of the breast. In order to explain these lesions, an extensive genetic study was performed. Results showed positivity for the presence of the tumor suppressor gene PALB2, whose presence had already been detected in a niece with breast cancer. The patient underwent different procedures to treat the lesions and currently she is symptom-free over 2 years of follow-up. Learning points: The presence of two rare neoplasms in a single person should raise the suspicion of a common etiology. To the best of our knowledge, this is the first case that shows the coexistence of DIPNECH and paraganglioma. The contribution of the PALB2 gene in the etiology of these rare neoplasms is a possibility.